(untitled) (Revista Sistemas de Producción Agroecológicos, 2012)
This work was performed to determine the major diseases can be transmitted through the importation of live animals, products and byproducts of cattle, pigs and poultry, which may affect the status of the country both in the animal area as public health is equally important to know the health measures provided by Colombia for the prevention of endemic animal diseases and exotic species listed above, because as our mission veterinarians working for animal health in the country. Knowledge of preventive health programs and disease control allows greater participation in international markets. We conclude that the products and by-products of bovine correspond to the increased volume of imports into Colombia during the years 2007-2009, followed by avian species and finally swine, according to statistical reports of the Colombian Agricultural Institute, for 2007 the percentage of imports of bovine origin was 40%, 39% avian and swine from 21% for the year 2008 the share of imports of bovine origin was 53%, 28% avian and swine and 19% for the year 2009 the share of imports of bovine origin was 46%, 35% avian and swine from 19% U.S. being the largest exporter of products and animal by-products in terms of these three species. Within the main diseases associated with the importation of animal products and byproducts of cattle, pigs and poultry, which affect not only animal health but also represent a public health problem because they are zoonotic type Bovine Spongiform Encephalopathy, Paratuberculosis, Brucellosis, Leptospirosis, trichinellosis, New Castle, Cysticercosis, Salmonellosis, Avian Influenza and Rabies. The Colombian Agricultural Institute (ICA) is a state agency responsible for preventing the entry into airports, ports and border crossings of pathogens that may affect animal health or public health, for this makes operating procedures and physical and documentary inspections, seizures, reembarques and cremation.